Cardiotonic Steroids-Mediated Na+/K+-ATPase Targeting Could Circumvent Various Chemoresistance Pathways - Mijatovic, Tatjana; Kiss, Robert (Planta Medica, 2013)
Many cancer patients fail to respond to chemotherapy because of the intrinsic resistance of their cancer to pro-apoptotic stimuli or the acquisition of the multidrug resistant phenotype during chronic treatment. Previous data from our groups and from others point to the sodium/potassium pump (the Na+/K+-ATPase, i.e., NaK) with its highly specific ligands (i.e., cardiotonic steroids) as a new target for combating cancers associated with dismal prognoses, including gliomas, melanomas, non-small cell lung cancers, renal cell carcinomas, and colon cancers. Cardiotonic steroid-mediated Na+/K+-ATPase targeting could circumvent various resistance pathways. The most probable pathways include the involvement of Na+/K+-ATPase β subunits in invasion features and Na+/K+-ATPase α subunits in chemosensitisation by specific cardiotonic steroid-mediated apoptosis and anoïkis-sensitisation; the regulation of the expression of multidrug resistant-related genes; post-translational regulation, including glycosylation and ubiquitinylation of multidrug resistant-related proteins; c-Myc downregulation; hypoxia-inducible factor downregulation; NF-κB downregulation and deactivation; the inhibition of the glycolytic pathway with a reduction of intra-cellular ATP levels and an induction of non-apoptotic cell death. The aims of this review are to examine the various molecular pathways by which the NaK targeting can be more deleterious to biologically aggressive cancer cells than to normal cells.
Keywords: Na+/K+-ATPase; sodium pump; cardiotonic steroids; cardenolide; bufadienolide; cancer chemoresistance; multidrug resistance